Rediseño de componentes para prensa-estopa en generador de la PCH El Popal (2020)
From the design, one of the main challenges is the improvement of industrial processes that lead to having efficient productive sectors for the development of the country. In the Colombian industry, the energy sector is one of the pillars, one of its main sources being hydroelectric energy, since Colombia is a country where one of the most abundant resources is water. Among the country's hydroelectric plants is the small hydroelectric plant (PCH) El Popal SA Esp, located in Cocorná Antioquia. From periodic inspections and maintenance, abnormal wear has been observed in some components of the turbine. Currently, the PCH has a complementary system for the correct operation of the generating units called press-packing, which controls the possible entry of turbine water through the shaft in the direction of the generator and associated equipment; However, in recent months there have been several interruptions in the operation to carry out corrective maintenance due to water leaks, which has implied losses in time and incurred financial expenses. Therefore, in the present work a possible redesign of the press-packing components is studied and evaluated, taking into account the measurements and tolerances that exist between the shaft and the turbine cover to avoid the passage of water between the turbine and the bearing without modifying other essential parts of the equipment; in order to optimize the process and reduce maintenance costs and time.